Solvent-Free Lipase-Catalyzed Synthesis of Diacylgycerols as Low-Calorie Food Ingredients - Vázquez, Luis; González, Noemí; Reglero, Guillermo; Torres, Carlos (Frontiers in Bioengineering and Biotechnology, 2016)
Problems derived from obesity and overweight have recently promoted the development of fat substitutes and other low-calorie foods. On the one hand, fats with short and medium chain fatty acids are a source of quick energy, easily hydrolyzable and hardly stored as fat. Furthermore, 1,3-diacylglycerols are not hydrolyzed to 2-monoacylglycerols in the gastrointestinal tract, reducing the formation of chylomicron and lowers the serum level of triacylglycerols by decreasing its re-synthesis in the enterocyte and its metabolism and absorption by the enterocyte are limited in comparison with the TAG, reducing chylomicron formation. In this work these two effects were combined to synthesize short and medium chain 1,3 diacylglycerols, leading to a product with great potential as for their low-calorie properties. Lipase catalysed transesterification reactions were performed between short and medium chain fatty acid ethyl esters and glycerol. Different variables were investigated such as the type of biocatalyst, the molar ratio FAEE:glycerol, the adsorption of glycerol on silica gel or the addition of lecithin. Best reaction conditions were evaluated considering the conversion intopercentage of 1,3-DAG produced and the reaction rate. Except Novozym 435 (Candida antarctica), other lipases required the adsorption of glycerol on silica gel to form acylglycerols. Lipases that gave the best results with adsorption were Novozym 435 and Lipozyme RM IM (Rhizomucor miehei) with 52% and 60.7% of DAG at 32 h, respectively. Because of its specificity for sn-1 and sn-3 positions, lipases leading to a higher proportion of 1,3-DAG vs 1,2-DAG were Lipozyme RM IM (39.8% and 20.9%, respectively) and Lipase PLG (Alcaligenes sp.) (35.9% and 19.3%, respectively). By adding 1% (w/w) of lecithin to the reaction with Novozym 435 and raw glycerol the reaction rate was considerably increased from 41.7% to 52.8% DAG at 24 h.